Invigorating Entrepreneurial Spirit among Workforce - Aned O, Al Mutairi; Alya O, Al Mutairi (International Journal of Management and Sustainability, 2013)
With the key intent of stimulating entrepreneurial spirit among the workforce, this paper identifies the diverse entrepreneurial qualities required to propel the entrepreneurial spirit unremittingly. These relevant personal skills and strategies of New Venture Creation further aid in the successful creation and subsequent maintenance of an entrepreneur business. Prior to application of the identified skills, this paper vividly demonstrates the importance of such skills to any entrepreneurial business entity. This helps in New Venture Creation whilst aiding the businesses’ sustainability. Therefore, the through proper application of the knowledge attained as well as skills identified, the entrepreneur manages to depict dynamism by consistently exploring different entrepreneurial opportunities. Although these skills tremendously boost the entrepreneur’s spirit, they also create opportunities for the business to explore new and diverse opportunities thus circling back to enhancing entrepreneurial spirit. Furthermore, the paper seeks to make out the possible ways of constantly improving these entrepreneurial skills and in turn encouraging their adoption and consequent utilization among workforce. Further incorporation of knowledge attained from research projects on organizational climate, management support and reward and resource availability similarly focuses the paper to invigorating entrepreneurial spirit among workforce.